Pengaruh Penggunaan Metode Talking Stick Dan Kebiasaan Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X MAN 3 Kota Padang - Willy Septiani Putri; Sri Wahyuni; Jimi Ronald (STKIP PGRI Sumatera Barat, 2022)
This study aims to analyze the Influence of the Use of Talking Stick Methods and Study Habits on the Economic Learning Outcomes of Class X Students in MAN 3 Padang City. Based on the analysis of data it is known that both classes of samples are usually distributed and homogeneous. The results of the hypothesis test through two way ANOVA results are as follows: 1) The first hypothesis obtained a sig value of 0.000, this means that the sig value. less than the value (a= 0.05 (sig.<(a) then thus the H0 accepted Ha rejected, so it can be concluded that the learning outcomes of students taught using the talking stick method are higher than those taught using conventional learning methods (discovery learning). 2) the second hypothesis, obtained the value of the sig. 0.000, this means that the value of the sig. less than the value (a = 0.05 (sig.< (a) then thus H0 accepted Ha rejected, so it can be concluded that students who have good study habits have high learning outcomes than the learning outcomes of students who have poor study habits. 3) the third hypothesis, obtained the value of the sig level. = 0.401, this means that the value of sig. is greater than the value (a = 0.05 (sig. < (a) then thus the H0 rejected Ha accepted, so that there is no interaction of learning models talking sticks and study habits towards student learning outcomes.